Identification of two phase flow regimes by void fraction measurements - Tri, Bui Dinh (Vietnam Journal of Mechanics, 2005)
This paper will present a method to identify flow patterns (bubble & slug flow) in vertical air-water two-phase flow by void fraction measurement (using an impedance probe) at Inst. of Mechanics Hanoi.